Application of Supply Chain Management Practices in Banks: Evidence from Indonesia - Dewi Anggraini; Azreen Hamiza; Caturida Meiwanto Doktoralina; Sri Anah (International Journal of Supply Chain Management, 2018)
The present study aims to examine the idea of supply chain management in the financial institutions like banks in the region of Indonesia. After the detailed examination of existing literature current research work has developed a model for the supply chain in financial perspective with its physical implication as well. By focusing on 5 multinational banking firms, current research work has studied the causal association between the SCM and banking sector for their performance. Findings of the study explain that both SCM and working of financial institutions are highly linked to each other. In short, SCM is a meaningful tool for the banking firms or the organizational performance and various departmental heads are very much aware to SCM practices for the greater banking performance. The core limitations of the study are very limited sample size and just focusing on the one selected banking category (International banks). However, the practical implications of the study are very much significant.